Cold-formed steel portal frames in fire: Full-scale testing and finite element analysis - Johnston, R.; Lim, J.; Lau, Hieng Ho; Xu, Y.; Sonebi, M.; Armstrong, C.; Switzer, C.; Mei, C. (2014)
A full-scale, non-uniform natural fire test on a cold-formed steel portal frame building is described. The results of the fire test are used to validate a non-linear, elasto-plastic, finite element shell idealisation, for the purposes of later forming the basis of a performance-based design approach for cold-formed steel portal frames at elevated temperatures. The test building had a span of 8m, height-to-eaves of 2.2m, length of 10m, with a frame spacing of 2.5m. The member and connections of the frame were constructed entirely from cold-formed steel and the eaves and apex joints were classified as semi-rigid. In order to reduce the influence of diaphragm action, the cladding was detailed to act independently from the frames. The frame collapsed with an eventual inwards asymmetrical collapse mechanism at 714°C, with collapse being due to member buckling rather than failure of the screws or joints. The collapse temperature predicted using the shell idealisation was 682°C, with a deformed shape similar to that observed in the fire test.